First description of mantis shrimp, Miyakella nepa (Latreille, 1828), feeding preference behaviour in captive conditions - Li-Yen Lee (Elsevier, 2022)
Mantis shrimps are stomatopod crustaceans yet to be successfully cultured on a commercial scale due to several impediments, namely their aggressive behaviour in a communal setting and a lack of understanding on their feeding regime during different life stages in captivity. Local adult mantis shrimp, Miyakella nepa (Latreille, 1828), were observed in laboratory conditions to obtain baseline data of feeding preference behaviour. M. nepa were kept individually, with tube shelter provided, either with or without sand substrate, to understand their burrowing behaviour (n = 16). Most of the stomatopods remained within the tube (>90% of observation time) during pre-feeding but ventured out of the shelter (47–60% of observation time) when feed was provided. They were presented with one or two types of natural feed to identify affinity towards specific food. During the 15-minute observation, mantis shrimps (n = 20) were placed in a testing arena and presented with natural feed. The fastest time for mantis shrimps to approach feed, indicating attractiveness, is fish, clam, shrimp, squid and then polychaetes. About 57% made an approach towards the squid, but none of them managed to consume it. Subsequent feeding preference observation included a combination of two diets presented at the same time: fish-shrimp, fish-clam, fish-polychaete, shrimp-clam, shrimp-polychaete, and clam-polychaete. Observations of M. nepa feeding preference in captivity revealed that they can consume several types of feed. It is recommended to provide fish as they were preferred to all other types of diets comparatively when presented without other food choice, and/or clams as they indicated high attractiveness due to short approach time when presented with choice. Mantis shrimps are considered opportunistic predators in the wild and M. nepa do not show a clear pattern with significant difference of preference towards any single type of natural feed presented in the laboratory setting.